Heavy metal analysis of different type of agriculture soil by aas atomic absorption spectrometry - Rusli, Nor Farah Emyliana Mohd (Universiti Sains Malaysia, 2017)
Heavy metals are natural constituents of the Earth's crust. They are stable and cannot be degraded or destroyed, therefore they tend to accumulate in soils. Thus heavy metal composition in soil can serve as fingerprint of the land as soil can be used to locate crime scene. This study investigate the concentration heavy metal of Cu, Cd, Cr, Pb and Zn in surface soil sample from different types of agriculture soil by using Atomic Absorption Spectrometer (AAS). The concentration of Cu, Cd, Cr, Pb and Zn in the surface soil sample from different types of agriculture soil of palm oil, sugarcane, rubber, lime and banana were determined. Before analyzed by AAS, sample pretreatment method was employed. Overall concentration (mg/kg) of Cu, Cd, Cr, Pb and Zn in the soil samples from palm oil was found to be Cu (2.887), Cd( 3.468), Cr (2.273), Pb (ND) and Zn(12.194), Sugarcane: Cu ( 4.278), Cd (2.918), Cr ( 7.711), Pb (ND) and Zn ( 23.216), Rubber: Cu( 14.735), Cd (4.243), Cr ( 9.033), Pb ( 7.890) and Zn (25.525),Lime: Cu (27.377), Cd ( 3.702), Cr (14.212), Pb ( 27.112) and Zn( 32.222), Banana: Cu (68.162), Cd (4.530), Cr (17.173), Pb (63.798) and Zn (40.088). The differences concentration of heavy metal in soil can be used in forensic analysis of soil to differentiate the type of agriculture soil and this data can help in investigation that involved soil analysis. The concentrations of Cu, Cd, Cr, Pb and Zn in all different types of agriculture soil were below the USEPA standard of heavy metal in soil. The accuracy of the optimized acid digestion procedure was evaluated by recovery studies. The recoveries of the metals were in the range of 64.00%-91.54%.